Diverse effects of beta-tubulin mutations on microtubule formation and function (The Rockefeller University Press, 1988)
We have used in vitro mutagenesis and gene replacement to construct five new cold-sensitive mutations in TUB2, the sole gene encoding beta- tubulin in the yeast Saccharomyces cerevisiae. These and one previously isolated tub2 mutant display diverse phenotypes that have allowed us to define the functions of yeast microtubules in vivo. At the restrictive temperature, all of the tub2 mutations inhibit chromosome segregation and block the mitotic cell cycle. However, different microtubule arrays are present in these arrested cells depending on the tub2 allele. One mutant (tub2-401) contains no detectable microtubules, two (tub2-403 and tub2-405) contain greatly diminished levels of both nuclear and cytoplasmic microtubules, one (tub2-104) contains predominantly nuclear microtubules, one (tub2-402) contains predominantly cytoplasmic microtubules, and one (tub2-404) contains prominent nuclear and cytoplasmic microtubule arrays. Using these mutants we demonstrate here that cytoplasmic microtubules are necessary for nuclear migration during the mitotic cell cycle and for nuclear migration and fusion during conjugation; only those mutants that possess cytoplasmic microtubules are able to perform these functions. We also show that microtubules are not required for secretory vesicle transport in yeast; bud growth and invertase secretion occur in cells which contain no microtubules.